Developing a Typology of Competitive Intelligence Proficiency: The Case of French SMEs and Funded Intervention Programs - LARIVET, Sophie; SMITH, Jamie; WRIGHT, Sheila (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2016)
This article reports on a study about the evolution of SMEs’ Competitive Intelligence (CI) practices, in the French context of a public CI policy. Fifteen Directors of CI programs at Chambers of Commerce were interviewed and 176 SME decision-makers surveyed. An important contribution is a typology of SMEs including perceived constraints, advisors, and attitudes towards CI. We conclude that SMEs find appropriate help through publicly funded programs at the early stages of CI practice, whereas consultants are effective to guide them towards higher levels of performance. The findings are of significance to SME managers, CI providers and policy decision-makers.